The Role of the Automated Implantable Cardioverter Defibrillator (AICD) for Secondary Prevention in the COVID-19 Era - Doodnauth, Andrew V (Cureus, 2021)
Life-threatening arrhythmias have been variably reported among patients hospitalized for COVID-19 infection. Sudden cardiac arrest (SCA) in COVID-19 patients is an alarming concern for clinicians. Multiple factors play an important role in the development of SCA in patients with severe systemic illness. We describe a case of COVID-19 in a New York City hospital in Spring 2020 that rapidly developed SCA and, before discharge, received a single lead transvenous implantable cardioverter defibrillator for secondary prevention. This case highlights the use of an automated implantable cardioverter-defibrillator as a secondary preventive measure irrespective of left ventricular function as a means of preventing recurrence of SCA as a sequela of COVID-19.